Relación entre el capital social y el desempeño de las organizaciones agro-productivas del Ecuador - Vega Chamba, María Evelina (2021)
The objective of this research work was to analyze social capital, identify its dimensions and relate this concept to the income of agro-productive organizations that appear in the administrative records of the Ministry of Agriculture and Livestock of Ecuador. From the analysis of main components, a social capital index was constructed that identified 4 of the dimensions indicated by the literature, which are closely related to the principles of the social and solidarity economy: participation and trust; network, cooperation and awareness and local reciprocity. According to the regression model carried out, it was evidenced that the relationship between the dimensions of social capital and the income of agro-productive organizations is positive, ratifying what has been described in several studies, regarding that higher levels of social capital are related to benefits in various scopes.